Evaluation of mucin histochemistry in relation to p63 expression in nodular hyperplasia and adenocarcinoma of prostate - Sweety, Rumana Afrin; Sultana, Shifayat; Islam, M. Ariful; Dewan, M. Rezaul Karim; Zhumur, Mahbuba; Jeba, Ruksana; Shaheen, Nazma (International Journal of Research in Medical Sciences, 2023)
Background: Prostate cancer is a leading cause of death in men. Nodular hyperplasia and adenocarcinoma are common causes of prostatic enlargement. Diagnosis of these lesions on routine biopsies can be difficult for pathologists. Immunohistochemical stain p63 can help, but it is costly and not widely available. The present study aimed to evaluate the usefulness of mucin histochemistry in relation to p63 expression in differentiating nodular hyperplasia and adenocarcinoma of prostate. Methods: This study was conducted in the department of pathology at Dhaka medical college from July 2018 to June 2020. 50 cases of prostatic lesions (25 NHP and 25 adenocarcinoma) were examined using histomorphology. The sections were stained with periodic acid Schiff (PAS) to identify neutral mucins and Alcian blue (2.5 pH) to identify acidic mucins. Additionally, p63 antibody was used in immunohistochemistry. Results: NHP showed positivity for neutral mucin (96% with PAS stain) but not for acidic mucin (Alcian blue stain), while prostatic carcinoma showed positivity for both neutral mucin (28%) and acidic mucin (44%). The grade group 1 tumors of prostatic carcinoma showed 100% positivity for acid mucin, with a decrease in Alcian blue staining as the grade increased. P63 was positive in 100% of NHP cases and negative in 100% of prostatic carcinoma cases. Conclusions: Positivity for acidic mucins with Alcian blue stain can be a helpful diagnostic tool to differentiate well differentiated adenocarcinomas from benign lesions where facility for p63 immuno-stain is not available and poor people who cannot afford the cost of immunohistochemistry.